PENGEMBANGAN TUJUAN PEMBELAJARAN PAI ASPEK KOGNITIF DALAM TEORI ANDERSON, L. W. DAN KRATHWOHL, D.R. - Khaidaroh Shofiya F.; Sukiman . (STAINU Purworejo, 2018)
The theory of cognitive learning in learning emphasizes a process that occurs in the human mind. The Cognitive domain of Bloom’s taxonomy often serves as a framework for categorizing objectives oflearning and education, designing tests, and designing curricula. The taxonomy in order covers: (1) knowledge, (2) comprehension, (3) application, (4) analysis, (5) synthesis, and (6) evaluation. The cognitive domains hold the opinion of Anderson and Krathwohl improved views to develop the learning objectives of the Bloom Taxonomy revision of Benyamin is remember, applying, applying, analyzing, evaluate, create. There are four categories in the dimension of cognitive knowledge is: factual knowledge, conceptual knowledge, procedural knowledge and metacognitive knowledge.